Distribution of Microplastics in the Marine Environment - Strafella, Pierluigi; López Correa, Matthias; Pyko, Ines Anna; Teichert, Sebastian; Gomiero, Alessio (Handbook of Microplastics in the Environment, 2021)
The increasing rate of worldwide plastic consumption and its release to the environment associated with a low degradation rate is resulting, nowadays, in its accumulation in all the ocean matrices, from sediment to water, in pelagic and benthic biota, from coastal to open ocean areas at each latitude. A big amount of manufactured plastic materials ends up in the oceans, floats on the sea surface, drifts in the water column, or sinks to the seafloor from the shorelines to the deep-sea. Consequently, microplastics are widely distributed in all the oceans, from the water surface to the sediments in the deep-sea, from the beaches to offshore. This is one of the critical global challenges, due to the fact that, having no borders, this pollutant affects the entire world ocean, from polar areas to the equator. Nowadays, the big deal is to understand the hotspot accumulation of microplastics, their sources and distribution mechanisms, to provide real actions to prevent an environmental worsening and to reduce the possible microplastic entry paths into the oceans. The purpose of this chapter is to give an exhaustive overview on the distribution and occurrence of microplastics in the worldwide oceans, considering the different matrices present in the sea environment, from the beach to the water surface and column, to the marine sediments, taking into account the peculiar characteristics of the matrices from the shoreline to offshore, from sublittoral to the hadal environments.
CRIS-Team Scopus Importer:2024-12-16